Molecular Properties of Carboxymethyl Chitosan and Its Complexes with Curcumin and Nicotinamide in Drug Delivery Applications: Molecular Docking and Molecular Dynamic Study - Luthfiyah Hana Afiyah; Dwi Hudiyanti; Muhammad Cholid Djunaidi; Vivitri Dewi Prasasty; Suci Zulaikha Hildayani; Parsaoran Siahaan (Jurnal Kimia Sains dan Aplikasi, 2024)
Carboxymethyl chitosan (CMCs) is a chitosan-derived compound usually used as a carrier matrix in drug delivery systems. There are three types of CMCs based on the location of carboxyl group substitution: N-CMCs, O-CMCs, and N,O-CMCs. The ability of CMCs as a carrier is related to the ability of CMCs to interact with drug molecules. In this work, curcumin and nicotinamide were used as drug models. The ability of CMCs to interact with drug models can be observed by the amount of interaction energy generated when CMCs interact with curcumin and nicotinamide. The purpose of this study is to determine the interaction energy generated when CMCs interact with curcumin and nicotinamide using molecular docking and molecular dynamic methods. The results showed the interaction energy between O-CMCs, N-CMCs, and N,O-CMCs (2 and 3 monomers) with curcumin and nicotinamide, respectively, ranged from -17.08 to -13.37 and -12.05 to -11.00 Kj/mol. Conformational changes in molecular dynamic simulations affect bond-free energy, RMSD, and potential energy complex values.